2015
DOI: 10.3926/jiem.1784
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation on aquatic product cold-chain logistics

Abstract: Abstract:Purpose: The requirements for high quality and diversification aquatic products are increasing with the improvement of Chinese living standard. However, the distribution between the place of production and the place of consumption are uneven, which results in large cold-chain logistics demand for aquatic products. At present, the low-level development of cold chain logistics has a bad impact on the circulation of aquatic products in China. So it is very urgent to develop cold-chain logistics in China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…established an evaluation index system from four links, including cold chain logistics processing, transportation, cold storage and sales, and evaluated the risk of cold chain logistics for dairy products based on DNB approach. Wu et al (2015) constructed an AC-SST evaluation index model for cold chain logistics of aquatic products from the aspects of transportation quality, cost, efficiency and social benefits. Li et al (2015) established an evaluation index system from the aspects of response ability, transportation level, customer service, etc., and used the dynamic intuitive fuzzy VIKOR group decision-making model to evaluate the selection of cold chain logistics suppliers.…”
Section: Cold Chain Logistics Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…established an evaluation index system from four links, including cold chain logistics processing, transportation, cold storage and sales, and evaluated the risk of cold chain logistics for dairy products based on DNB approach. Wu et al (2015) constructed an AC-SST evaluation index model for cold chain logistics of aquatic products from the aspects of transportation quality, cost, efficiency and social benefits. Li et al (2015) established an evaluation index system from the aspects of response ability, transportation level, customer service, etc., and used the dynamic intuitive fuzzy VIKOR group decision-making model to evaluate the selection of cold chain logistics suppliers.…”
Section: Cold Chain Logistics Evaluationmentioning
confidence: 99%
“…According to the actual situation of cold chain logistics, the vulnerability of cold chain logistics can be divided into three characteristics: exposure, sensitivity and adaptability. Therefore, in this study, from the three dimensions of exposure (Salhi, 1994;Ji et al, 2016), sensitivity K 51,2 (Li, 2014) and adaptability (Kelly and Adger, 2000;Cardona et al, 2012), we established a novel assessment index system of cold chain vulnerability by considering the influence of Wu et al, 2015;Li et al, 2015;Defraeye et al, 2019;Beretta et al, 2019;Gogou et al, 2015;Wang et al, 2016;Shi et al, 2015;Zhang et al, 2018) factors such as personnel, equipment and facilities, environment, management, market and policy, as well as combination with expert survey methods while following the scientific, systematic and operational principles, which is shown in Table 2. On this basis, the twostage grey comprehensive measurement model of IF entropy is used to comprehensively 4.…”
Section: Determination Of the Assessment Index System For Cold Chain Vulnerabilitymentioning
confidence: 99%
“…The survey of the industry experts' insights about European food service supply chains showed that the industry is aiming at creating customer value (Darkow, Foerster, & von der Gracht, 2015). The cold chains of aquatic products were also discussed and it was shown that within certain temperature range, lower temperature brings higher profit level, and their findings encouraged better temperature control of cold chains (Wu, Deng, Zhang, & Zhang, 2015). One type of cold chains, i.e., the pharmaceutical supply chain was studied with a systematic review of research on managerial issues, and the research direction about structure of pharmaceutical supply chains was highlighted (Narayana, Pati, & Vrat, 2014).…”
Section: Perishable Products Cold-chain System and Value Chain Analmentioning
confidence: 99%
“…It is difficult to assess cold chain performance because cold chains differ from other types of product supply chains in certain ways. According to Wu et al (2015), the performance measurement system can be carried out in a simple and traditional manner, but the cold chain of fishery products has its own unique characteristics. A well-defined performance measurement system can be used to help with goal setting, performance evaluation, and determining future actions at the strategic, tactical, and operational levels (Gunasekaran et al 2001).…”
Section: Introductionmentioning
confidence: 99%